2015
DOI: 10.1088/1367-2630/17/3/033027
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of plasma mirror reflectivity and optical quality using double laser pulses

Abstract: We measure a record 96 ±2.5% specularly reflected energy fraction from an interaction with a plasma mirror (PM) surface preionized by a controlled prepulse and find that the optical quality is dependent on the inter pulse time delay. Simulations show that the main pulse reflected energy is a strong function of plasma density scale length, which increases with the time delay and reaches a peak reflectivity for a scale length of 0.3 μm, which is achieved here for a pulse separation time of 3 ps. It is found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 35 publications
2
27
0
1
Order By: Relevance
“…A double pulse was generated via the same module described in previous work, which investigated the optimisation of plasma mirror reflectivity [21], delivering a prepulse to main pulse energy of 1:10 and with variable delay of up to 100 ps. In total, 72±2 J of laser energy was delivered on target for the shots considered here, giving an average focused main pulse intensity of´-4 10 W cm 18 2 .…”
Section: Experimental Details 21 Methodsmentioning
confidence: 99%
“…A double pulse was generated via the same module described in previous work, which investigated the optimisation of plasma mirror reflectivity [21], delivering a prepulse to main pulse energy of 1:10 and with variable delay of up to 100 ps. In total, 72±2 J of laser energy was delivered on target for the shots considered here, giving an average focused main pulse intensity of´-4 10 W cm 18 2 .…”
Section: Experimental Details 21 Methodsmentioning
confidence: 99%
“…This is consistent with current theoretical models of laser absorption and EMP generation. Scott et al have shown that laser absorption is a strong function of plasma density and scale length [15] , which are both dependent on the pre-pulse delay. The longer the delay between the pre-pulse and main drive, the greater the pre-plasma expansion and the greater the transfer of laser energy to hot electrons.…”
Section: Pre-pulse Delaymentioning
confidence: 99%
“…This reflectance matches the values previously published with similar contrasts and intensities for s-polarized pulses reflecting from a PM. 7,19,20 Changing the input light's polarization from s-polarized to p-polarized provided a direct comparison of the magnitude A plot showing the published reflectance values from different PM studies and the year they were measured is given in Fig. 11.…”
Section: E Model Fit Parameter Resultsmentioning
confidence: 99%
“…The absorption levels of 18%-19% seen in the study of s-polarized light agree with previously published values from a self-triggered PM. 7,19,20 The absorbed energy directly relates to a drop in reflectance (as shown in Fig. 7(d)), and this parameter is used to vertically shift the plot to match the height of the experimental data.…”
Section: B Determination Of the Plasma Parametersmentioning
confidence: 99%